Institutionalization and trajectories of personal archives in Brazil - Crivelli, Renato [UNESP]; Bizello, Maria Leandra [UNESP] (My University, 2021)
The article covers the development of institutionalization of personal archives in the Brazilian archival scenario by means of the analysis of processes from three custodial institutions: IEB, Cpdoc and Mast. Administrative processes of collection incorporation were analyzed from the date of their foundations until 1999, with the aim of capturing the method of the selection practiced by the institutions be-fore their collection policies were published.
Institucionalización y trayectorias de archivos personales en Brasil
Institucionalização e trajetórias dos arquivos pessoais no Brasil
Keywords: institutionalization; manuscripts repository; personal archives